Reviewing Learning Styles Regarding Medical Students of Kerman University of Medical Sciences and Providing a Teaching Method Appropriate based on Their Views - Mahdi Darvishzade; Sakineh Sabzevari; Behshid Garrosi; Akbar Hassanzade (Kerman University of Medical Sciences, 2013)
Background & Objective: One of the most important factors in students learning is their learning style whose identification helps to produce an optimal and effective learning program This study aimed to determine the learning styles in medical students and providing an appropriate teaching method based on their views Methods: This crosssectional study was conducted in 2011 on 276 medical students who were chosen by proportional to size method The means of data collection was a questionnaire which included three parts ie demographic factors Kolbs learning styles and questions about teaching methods Then the data were collected and analyzed Results: Learning style of most of the students was assimilator (471%) and the order afterwards was divergent style (268%) convergent (185%) and accommodator (76%) respectively The most appropriate teaching methods from the viewpoints of students were concept attainment ward report and caseconference methods No statistically significant association was found between the learning style and the variables of age gender academic year and material status There was a statistically significant association between the habitat of students and their wish to continue study however in urban students was accommodator and in students who wanted to study in postgraduate levels learning style was divergent Conclusion: Considering note that medical students have chosen concept attainment ward report and caseconference methods as appropriate pattern of teaching for their training this results are helpful for medical education system so that to improve students learning The lecturers had better bring studentcentered approach in which learners have an active role to learn rather than uniform teaching method such as lectures